Anion Exchange Membrane Water Electrolysis Based on Nickel Ferrite Catalysts. Issue 1 (13th December 2022) - Caprì, Angela; Gatto, Irene; Lo Vecchio, Carmelo; Trocino, Stefano; Carbone, Alessandra; Baglio, Vincenzo
Abstract: A nickel ferrite was prepared by a liquid‐phase method and used as an oxygen evolution catalyst in an anion exchange membrane electrolyser. A complete physicochemical characterization of the catalyst was performed through X‐ray diffraction (XRD), Transmission electron microscopy (TEM) and X‐ray photoelectron spectroscopy (XPS). Then, the nickel ferrite was deposited by spray coating technique onto a Fumasep® FAA3‐50 anion‐exchange membrane to realize a catalyst‐coated membrane (CCM), and tested in a 5 cm 2 single cell setup in the so‐called zero‐gap configuration. At 60 °C and 2.2 V, a current density of 3 A/cm 2 was reached, which is higher than that obtained with NiO and IrO2 commercial catalysts. Moreover, a chronoamperometric test of 120 h highlighted the good stability of the synthesized catalyst. Abstract : Nickel ferrite for Anion Exchange Membrane Electrolyser : Home‐made nickel ferrite, characterised by low cristallyte size (3.3 nm), was employed as an oxygen evolution catalyst in anion exchange membrane water electrolyser achieving the highest current density values (at 2 V) among the non‐PGM‐anode‐based MEAs.